Integrating Artificial Intelligence in Indonesia’s Arbitration: Navigating Legal and Political Challenges - Herliana, Herliana; Widowati, Dyah Ayu (Yuridika, 2025)
As Indonesia explores the integration of artificial intelligence (AI) into its arbitration processes, it faces a complex landscape of challenges and opportunities. This study investigates how AI can enhance efficiency, transparency, and decision-making in arbitration, while also addressing significant legal and political concerns. From a legal perspective, the use of AI in arbitration raises issues of compatibility with existing laws, the need for ethical guidelines, and the protection of data privacy. Politically, the adoption of AI is influenced by the potential for shifting power dynamics, regulatory concerns, and the broader implications for national sovereignty and international relations. Through a detailed analysis of these factors, the study aims to provide insights into how Indonesia can effectively navigate the integration of AI in arbitration, balancing technological advancements with legal and political considerations. By offering recommendations for addressing these challenges, the research seeks to contribute to the development of a robust framework for AI-driven arbitration in Indonesia. This research finds that the legal political landscape influences how AI is regulated, with potential resistance from established legal institutions or political entities concerned about losing control or influence. From a legal perspective, AI systems can minimize biases or inaccuracies and potentially improve the impartiality and fairness of arbitration decisions. Current regulations may not fully address the unique challenges posed by AI, necessitating updates or new legislation to govern AI use in arbitration. It is therefore important to engage with political and legal stakeholders to address concerns and build consensus on the adoption of AI in arbitration.